Implementation of unsupervised learning models for analyzing the state's security level - Laktionov, Oleksandr; Shefer, Oleksandr; Laktionova, Iryna; Halai, Vasyl; Podorozhniak, Andrii (Національний технічний університет "Харківський політехнічний інститут", 2024)
The process of creating unsupervised learning models and their peculiarities in tasks of analyzing the state's security level has been investigated. Techniques for creating the basic k-means model and its improvement through the use of Pearson correlation as a distance metric have been considered. Determining cluster centers was performed by both the basic method and the Cochran's maps method. The optimal quality indicator, according to the results of clustering, was considered to be the model demonstrating the minimum value of the DaviesBouldin index. The proposed model for clustering the state's security level differs from existing ones by using as input estimates derived from a comprehensive indicator based on the principles of interaction and emergent properties. This allows obtaining advantages of the clustering model in terms of the Davies-Bouldin index.

Досліджено процес створення моделей навчання без учителя та особливості їх використання у задачах аналізу рівня безпеки держави. Розглянуто техніки створення базової моделі kmeans та її удосконалення за рахунок використання кореляції Пірсона як метрики визначення відстані. Визначення центрів кластерів проводилося базовим методом й методом карт Кохрена. Оптимальним показником якості, за результатами кластеризації вважалася модель, яка демонструє мінімальне значення індексу Девіса-Болдіна. Запропонована модель кластеризації рівня безпеки держави відрізняється від існуючих використанням у якості вхідних оцінок визначних на основі комплексного показника, котрий побудований на основі принципів взаємодії та емерджентності. Це дозволяє отримати переваги кластеризаційної моделі за ознакою індексу Девіса-Болдіна.
Впровадження моделей навчання без учителя для аналізу рівня безпеки держави
Keywords: state's security level; clustering models; linear scaling; factor interaction; learning models; моделі навчання; моделі кластеризації; лінійне масштабування; взаємодія факторів; безпека держави